About an optimal control for a "predator-prey" system - Pashko, S.V. (PROBLEMS IN PROGRAMMING, 2020)
We consider the system of Lotka-Volterra differential equations with two control variables and describe an optimal control, which provides a transition to a stationary point in a minimum time. We also found an optimal control for the limit case, on condition that the phase trajectories are located near a stationary point. Optimal trajectories of motion in the phase space are constructed; they look like spirals.Problems in programming 2020; 2-3: 287-294